Evaluasi Numerik Kinerja Condenser PLTU Unit 8 di PT. POMI Paiton - Suantara Darma Gede; Agus Setiawan Priyo; Moballa Burniadi (Politeknik Perkapalan Negeri Surabaya, 2018)
Condenser modeling to determine the performance of industrial condensers on a steampower-based energy generator. The effectiveness of condenser is very important, so the condenserperformance needs to be maintained. The efficiency of condenser work directly affects theperformance of turbine steam, which is an energy generator in the system. The saturation pressurein the industrial condenser before to the plugging process has the highest value of 27790.0 (Pa). Themaximum condensation rate value in the industrial condenser before the plugging process is0.00529579 (Kg/m3.s). The saturation temperature in the industrial condenser after the pluggingprocess has the highest value of 300.0 (oK). The maximum condensation rate value in the industrialcondenser after the pluging process is 0.00519625 (Kg/m3.s).